Comparative bioequivalence study of Pioglitazone tablets, 20 mg (JSC «Chimpharm», Kazakhstan) and Actos® Tablets, 30 mg («Eli Lilly Holdings, Takeda Global Research and Development Centre Europe Ltd») - A. K. Sariev; D. A. Abaimov; M. V. Shiryaev; E. Y. Styrova; S. A. Altynbekov; G. A. Dzholdygulov; V. N. Seryakov; Y. M. Budach; O. E. Kurilo (Фармакокинетика и Фармакодинамика)
Within the cross, a single, open, randomized study with a two-week washout period, the two sequences has been studied bioequivalence of tablet forms two pioglitazone 18 volunteers (30 mg dosage). Plasma samples were analyzed by a validated HPLC-MS/MS within 48 hours. Analyzed for drugs following pharmacokinetic parameters were calculated: AUC0-t, Cmax, tmax, Cmax /AUC. 90% confidence interval for log-transformed values of AUC0-t was 0.945 — 1.066 and Cmax — 0,871 — 1,044. The study concluded that bioequivalence compared pioglitazone drugs.